Assessment of investment risk in implementing enterprise procurement plan - Каткова, Татьяна Игоревна (Eastern-European Journal of Enterprise Technologies, 2014)
The problem of assessing the risk, arising from implementing the enterprise procurement plan is considered in the paper. The task of forming the procurement plan is reduced to solving a non-trivial problem of rational allocation of total investment between private investment projects, which together determine the selected procurement strategy. This problem is formulated as an optimization problem of mathematical programming with nonlinear separable objective function and linear constraints. The allocation efficiency criterion is profit, expected from implementing the procurement plan. The real difficulty in solving this problem is that the parameters of the objective function are random variables. Therefore, for any allocation of investment funds, which satisfies the constraints, the allocation efficiency criterion value also becomes random. In this connection, there is a specific problem of estimating the uncertainty level of the result of funds allocation between investment projects and the risk of possible solutions. The problem is solved as follows. First, statistical estimation of probability-theoretic characteristics of the objective function parameters is performed. Furthermore, by expanding the target function in a series, its linearization is made. After that, the calculation of the mathematical expectation and variance of a random value of the criterion is conducted that allows to determine interval estimates of the expected value of the profit, expected from implementing the selected procurement plan. It is clear that the obtained plan efficiency estimates are more informative than point and can be used when selecting the rational investment plan